Corrosion behaviour of 304L stainless steel and 5754 aluminium alloy for intermediate‐level radioactive waste containers. Issue 9 (25th January 2016) - André, B.; Fiers, B.; Creton, N.; Dirand, C.; Poinsot, D.; Faure, S.; Chevalier, S.
Abstract : 300 series stainless steels are the most common materials used in the manufacture of container for the intermediate storage of low‐ and intermediate‐level radioactive wastes. Today, aluminium alloys are being considered as an alternative as they would enable gamma measurements to be performed directly through the container. However, reactions which occur during storage, lead to the formation of corrosive species. An investigation and comparison of the corrosion behaviour of a 5754 aluminium alloy container with that of a 304L stainless steel container was realised. Samples were introduced in corrosive environment during several months and then characterised by SEM. Results allow or not to validate the use of this aluminium alloy as nuclear container material. Abstract : Due to the formation of corrosive species during the storage of low‐ and intermediate‐level radioactive waste, stainless steels are the most common materials used in the manufacture of container. This work investigates and compares a 304L stainless steel to a 5754 aluminum alloy. The objectives are to demonstrate that a 5754 AA is at least as resistant as stainless steel in particular conditions of wet corrosion by chlorides and nitrates.